Afforestation Techniques for Albizia lebbek Linn. (Benth) on Degraded Lands - Puri, D. N.; Gargya, G. R. (Indian Forester, 1995)
The studies on depth of soil working and soil amendments for successful establishment of Albizia lebbek on torrent land which has thin soil mantle over boulders and gravels of various sizes and shapes which constitutes 80% of the soil were carried out. Mixing of 30% partially decomposed leaf litter with excavated soil in holes show significantly superior growth in height as compared to refilling the holes with top soil (TS) and excavated soil (ES). The growth in holes of 50 cm depth was comparable with 100 cm depth holes refilled with top soil and mixture of leaf manure and excavated soil. The growth was 105 cm in 50 cm deep holes and 129 cm in 100 cm deep holes but were statistically at par at the age of 2 years. It is inferred that in torrent lands, 50 cm deep holes refilled with excavated soil and 30% mixture of partially decomposed leaf litter reduces the cost of soil working and gives good growth and establishment of Albizia lebbek.